High frequency of the 3R/3R polymorphism in the thymidylate synthase enhancer region in Indonesian childhood acute lymphoblastic leukemia - IDG Ugrasena; Sutaryo Sutaryo; Edy Supriadi; Laura Vroling; Jacqueline Cloos; Jan Hendrik Hooijberg; AJP Veerman (Paediatrica Indonesiana, 2006)
Background Deoxyuridylate monophosphate (dTMP) is neces-sary for DNA synthesis and thymidylate synthase (TS) is an im-portant target of cancer chemotherapy. Ethnic variations of thepolymorphic tandem repeat sequence in the enhancer region ofthe TS promoter has previously been described to influence theoutcome of acute lymphoblastic leukemia (ALL). A triple repeat isassociated with a higher TS gene expression than a double re-peat, resulting in poorer outcome of ALL patients treated with anti-folate methotrexate (MTX).Objective In this study, we determined the incidences of TS andmethylenetetrahydrofolate reductase (MTHFR) polymorphism andethnic variations between Indonesian and Caucasian ALL cellsamples obtained at diagnosis. Furthermore, we determined theinvolvement of TS polymorphisms in MTX sensitivity using athymidilate synthase inhibition assay (TSIA).Methods ALL cell samples were obtained at diagnosis from 101Indonesian and 157 Caucasian children treated with MTX prospec-tively. Genotyping for TS and MTHFR was analyzed by Genescanand Lightcycler. TS polymorphism was determined by PCR assayand MTHFR polymorphism and was analyzed by melting curveanalyses on lightcycler.Results Homozygous TS triple repeats were more than twice ascommon in Indonesian samples (76.3%) than in Caucasian samples(33.1%). Heterozygotes of the MTHFR mutations were seen in 15%of the screened Indonesian samples.Conclusion There are significant ethnic variations in TS generegulatory elements of leukemic cells. A difference was found be-tween the MTX sensitivity and a double or triple repeat in the Cau-casian ALL group. The samples with a triple repeat show a shift intheir distribution towards hypersensitivity to MTX. Further investi-gation on Indonesian samples may give insight in the role of poly-morphisms in MTX sensitivity